KEARIFAN ORANG MINAHASA DI PERANTAUAN - , Gloridei. L. Kapahang, SPsi, Prof. JE. Prawitasari, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study was aimed to determine whether there was interaction effect between gender, education level, and developmental age of Minahasa people wisdom overseas. In addition, it also want to find out if there was a difference between nomads Minahasa wisdom-sex male and female, between nomads Minahasa with secondary and higher education levels, and whether there were differences among the nomads Minahasa wisdom that has the age range of adolescent, early adulthood and late adulthood. Wisdom was measured using an adapted scale from Monica Ardelt (2003) named the Three-Dimensional Wisdom Scale (3D-WS). The scale has three dimensions, they were: the cognitive, reflective, and affective dimensions. These three dimensions were then combined with the five human qualities of Minahasa people formulated by Tilaar (1991), they were: the existential consciousness, sociality, historicity, insight into the future, and faith. The scales ware given to the Minahasa people where living in Special Region of Yogyakarta. The study stated that there were no interaction effect between gender, education level and developmental age of Minahasa people wisdom overseas. This was indicated by the F value 0.807 and significance 0,372 which was the value was far below the Ftable (2,71). Likewise, the results of research on sex group, education level, and developmental age did not reveal any significant differences equally